Penerapan QR Code dan Vigenere Cipher Dalam Sistem Pelaporan Juru Parkir Ilegal - Ade Zulkarnain Hasibuan; Munjiat Setiani Asih; Herlina Harahap (Query: Journal of Information Systems, 2019)
The number of illegal parking attendants creates problems around us, especially the losses received by the regional government. Parking money that should have contributed to regional income, but because of the presence of illegal parking attendants did not make the slightest contribution to the local government. Another problem is that the parking attendant often gives tariffs outside the normal tariff, so that the people are harmed. Therefore, with the development of current technology, it can help the public to report the illegal parking attendants, the system created in this study provides a solution where the parking lot business card will be given a QR Code marker, the public can scan the QR Code on the id card the parking attendant. If the parking attendant is indicated to be illegal, the public can report it directly using the application on their smart phone. In addition, the information contained in the QR Code is encrypted using vigenere cipher cryptography, it is intended that the information is guaranteed authentic and cannot be falsified by certain parties that aim to take advantage.Keywords:  QR Code, Parking Attendant, Smart Phone, Cryptography, Vigenere Cipher